Root growth impact on soil hydraulic conductivity during wetting and drying circles - Yuliana,; Apriyono, Arwan; Kamchoom, Viroon (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Saturated hydraulic conductivity (Ksat) plays a crucial role in the hydrological cycle by influencing water absorption and availability for assessing slope stability, erosion control and developing more resilient agricultural practices. On the other hand, vegetation and climate would play a significant role in influencing the variations in soil infiltration. This study aims to comprehensively explore the dynamic interplay between plant root formation, desiccation crack and seasonal changes on Ksat. The research employs the double ring infiltrometer test to estimate Ksat during wetting and drying circles. Prior to the double ring test, root growth patterns were observed using a minirhizotron and then was analysed as Root Area Ratio (RAR). The study reveals that Vetiver roots reduced crack intensity factor (CIF) compared to bare soil. Additionally, roots are pivotal in creating preferential flow pathways which results in higher Ksat compared to that in bare area. Dry periods significantly increased Ksat, with a 16-fold rise in vegetated areas due to root growth.